Rationale and design of the German-speaking myeloma multicenter group (GMMG) trial HD6: a randomized phase III trial on the effect of elotuzumab in VRD induction/consolidation and lenalidomide maintenance in patients with newly diagnosed myeloma - Salwender, Hans; Bertsch, Uta; Benner, Axel; Raab, Marc-Steffen; Hillengaß, Jens; Hose, Dirk; Huhn, Stefanie; Hundemer, Michael; Jauch, Anna; Seidel-Glätzer, Andrea; Goldschmidt, Hartmut (BMC cancer, 2019)
Despite major advances in therapy, multiple myeloma is still an incurable malignancy in the majority of patients. To increase survival, deeper remissions (i.e. CR) translating into longer PFS need to be achieved. Incorporation of new drugs (i.e. bortezomib and lenalidomide) as induction and maintenance treatment in an intensified treatment concept, including high dose melphalan (200 mg/m2), has resulted in increased CR rates, and is considered the standard of care for younger patients. Elotuzumab in combination with lenalidomide and dexamethasone has given better results as lenalidomide and dexamethasone alone in a phase III trial. The GMMG-HD6 trial will be the first phase III trial investigating the role of elotuzumab in combination with bortezomib, lenalidomide and dexamethasone (VRD) induction/consolidation and lenalidomide maintenance within a high dose concept.